PP.21.29: ACE-INHIBITORS (ACE-I) AND ANGIOTENSIN RECEPTOR BLOCKERS (ARB) IN THE ELDERLY. (June 2015) - Guarnieri, A.; Bainotti, S.; Moggia, E.; Ferrando, C.; Pacitti, A.
Abstract : Objective: ACE-I and ARB are widely prescribed in any age group. The general applicability of the recommendations of the large RAAS blockade trials to especially the older patient population reserve some doubts because several trials were short term studies, often enrolling patients with relatively few comorbid conditions and a very strict clinical control. The aim of the study was to evaluate the incidence and course of Acute Kidney Injury (AKI) due, according to clinical data and medical history, to the use of ACE-I or ARB in old patients hospitalized in our renal care unit. Design and method: Retrospective study of all patients over the age > 75 years admitted form 1/1/2009 to 12/31/2013. 55 patients (18% of total AKI) affected by AKI due to RAAS interfering drugs, 27 men and 28 women, mean age 82 years, treated with ACEI-(35), ARB-(19), ACE-I + ARB-(1). Concurrent e-GFR < 60 mL/min/1.73mq 89%, CV-disease 53%, diabetes 29%, pulmonary-disease 29%, multiple disease 33%. AKIN stages: 1 29%, 2 11%, 3 60%. AKI triggered by: enteritic syndrome 49%, use of diuretics with simultaneous reduction on fluid intake 44%, pneumonia 5%, NSAID use 2%. Results: Average days of hospitalization 8.5 +/- 4.5. Blood chemistry: Figure. No caption available. Two patients needed hemodialysis with subsequent functional recovery. Two patients died with AKI without need for dialysis. Conclusions: Our data understimate the true incidence of the disease because not infrequently patients with such features are hospitalized in other medical departements. However some considerations are possible: 1. The incidence remained constant over the observed years without seasonal variations. 2. In 44% of cases, only a reduction in fluid intake occured, without any significant intercurrent disease. 3. After all the prognosis was benign, in 96% a functional recovery occured and the mean length of hospitalization was comparable to the annual average. 4. No absolute controindications to RAAS blockade in old patients, but extreme caution and stop in risk of hypovolemia.